The Role of Business Risk in the Capital Structure of Islamic Commercial Banks with Company Size as a Moderating Variable - Fauziah Nur Hutauruk (Indonesian Economic Review, 2026)
This study aims to analyze the effect of business risk on capital structure with firm size as a moderating variable in Islamic Commercial Banks in Indonesia. Business risk is proxied by Non-Performing Financing (NPF), while capital structure is measured using the Capital Adequacy Ratio (CAR). The research population includes all Islamic Commercial Banks operating in Indonesia during the 2021–2024 period. Using a purposive sampling technique, eight Islamic Commercial Banks were selected as the research sample. Panel data regression analysis (pooled data) was employed as the analytical method using EViews 10 software. The results indicate that business risk, as measured by NPF, has no significant effect on capital structure (CAR). Furthermore, firm size does not moderate the relationship between business risk and capital structure. These findings suggest that the level of problematic financing does not play a decisive role in determining capital structure decisions in Islamic Commercial Banks during the observed period. This study contributes to the existing literature by extending empirical evidence on the direct relationship between business risk and capital structure in Islamic banking, an area that has not been extensively examined in previous studies. Practically, the results are expected to provide insights for bank management and regulators in formulating more effective risk management and capital adequacy policies.